Alfabet / alphabet : a memoir of a first language - De Meijer, Sadiqa, 1977- (Palimpsest Press, 2020)
Alfabet / Alphabet is the record of Sadiqa de Meijer's transition from speaking Dutch to English. Exploring questions of identity, landscape, family, and translation, the essays navigate the shifting cultural currents of language by using an eclectic approach to storytelling.